2016
DOI: 10.1002/cam4.817
|View full text |Cite
|
Sign up to set email alerts
|

peIF4E as an independent prognostic factor and a potential therapeutic target in diffuse infiltrating astrocytomas

Abstract: Malignant transformation in tumors is a complex process requiring accumulation of numerous oncogenic abnormalities. Brain tumors show considerable phenotypic and genetic heterogeneity. In a series comprising diffuse infiltrating astrocytomas (DIA) and reactive gliosis, we investigated the main factors associated with signaling pathways. We assessed expression levels and their association with tumor progression and survival. We studied 19 grade II astrocytomas, 25 anaplastic astrocytomas (grade III), 60 gliobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Using patient‐derived glioma TMAs, we confirmed that Ccnd1 expression is higher in GBM than in grade I and II astrocytoma biopsies (Figure A,B) . However, only a small proportion of cells showed clear cytoplasmic signal for Ccnd1 (Figure C).…”
Section: Resultssupporting
confidence: 55%
“…Using patient‐derived glioma TMAs, we confirmed that Ccnd1 expression is higher in GBM than in grade I and II astrocytoma biopsies (Figure A,B) . However, only a small proportion of cells showed clear cytoplasmic signal for Ccnd1 (Figure C).…”
Section: Resultssupporting
confidence: 55%
“…eIF4E is essential for ribosomal recruitment and the initiation of translation [33]; eIF4E binds eIF4A and eIF4G to form the eIF4F complex that binds target mRNAs. In this system, eIF4E appears to be key in the regulation of translation initiation, as it physically binds the mRNA and is the least abundant initiation factor [34]; the interface of these genes with miRNAs is supported given the role of miRNAs is post-transcriptional. It has a sole phosphorylation site that interacts with either eIF4G or non-phosphorylated 4E-BP1; the PI3-Akt-mTOR pathway phosphorylates 4E-BP1 so that it releases eIF4E, allowing binding to eIF4G [34].…”
Section: Discussionmentioning
confidence: 99%
“…In this system, eIF4E appears to be key in the regulation of translation initiation, as it physically binds the mRNA and is the least abundant initiation factor [34]; the interface of these genes with miRNAs is supported given the role of miRNAs is post-transcriptional. It has a sole phosphorylation site that interacts with either eIF4G or non-phosphorylated 4E-BP1; the PI3-Akt-mTOR pathway phosphorylates 4E-BP1 so that it releases eIF4E, allowing binding to eIF4G [34]. Thus eIF4E is important in the convergence of the TGF-β and Akt pathways, and its dysregulation is believed to be an important downstream regulator of Akt's action in tumorigenesis [6].…”
Section: Discussionmentioning
confidence: 99%
“…MNK activation and subsequent phosphorylation of eIF4E are negative prognostic factors for several cancers including malignant gliomas (4447). In addition to regulating cap-dependent mRNA translation, eIF4E also promotes nuclear export of specific eIF4E-sensitive oncogenic mRNAs through a process that is activated by MNK-mediated eIF4E phosphorylation (48, 49).…”
Section: Discussionmentioning
confidence: 99%